Needs in The Thinking of Abraham Maslow and Maqashid Sharia - Ulum, Miftachul; Mun'im, Abdul; Maghfuri, Rahmah Salsabila Al (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
Everyone is always faced with the fulfillment of unlimited needs. The purpose of this study is to examine the levels of human needs according to Abraham Maslow and maqasid sharia. A normative and sociological research methodology approach that bases analysis on social phenomena. The results of the observation of Abraham Maslow's theory are studied in the discipline of sharia. The concept of maqasid sharia places religion as a benchmark in order to save human souls. The levels of need in the sharia maqasid concept include hifdz addin (preservation of religion), hifdz al nafs (preservation of the soul), hifdz al mal (preservation of property), hifdz aql (preservation of reason), and hifdz al nasl (preservation of offspring). Abraham Maslow stated that someone who has achieved self-actualization is universal, will be able to uphold the values ??of goodness in dealing with others even though it is not religious. The concept of maqasid sharia views the achievement of human self-actualization as humans will tend to be more obedient to God and always do good to others